Pablo Picasso: In Search of Language - Mallen, Enrique (International Journal of Culture and History, 2024)
The article explores Picasso’s multiple influences early in his career as he searched for a language that best expressed his vision of reality. Already the first critics, such as Félicien Fagus for his first exhibition at Galerie Vollard, mentioned the impact on the young Spaniard of a wide range of modern painters in addition to the great classical masters. Many of the identifiable periods in his extensive career can be associated with one or more influential artists: Casas, Rusiñol, Steinlen, Munch during the Modernist years in Barcelona; Toulouse-Lautrec, Renoir, Degas, Van Gogh and others in the first years in Paris; El Greco, Nonell, Puvis, among others during the Blue Period; Matisse, Redon, and others, in the Rose Period; Gauguin later on, etc., etc. These are just a few of the many artists whose styles Picasso explored in numerous ways. Their influence often occurred in complex combinations and would not fully disappear from his works once their incidence had left their imprint. Thus one can find the presence of El Greco or Van Gogh as late as the last years of Picasso’s life. Here we will focus on their influence in the period that preceded Cubism, Picasso’s first truly original language.